Efektivitas dan Tantangan Pengelolaan Barang Milik Daerah Menggunakan Sistem Informasi Manajemen-Barang Milik Daerah (SIMDA- BMD) - Agung Zulqurnaen; Nur Asiah (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2026)
Abstract: This study aims to determine the effectiveness and obstacles of implementing the Regional Asset Management Information System (SIMDA-BMD) in improving the efficiency and accountability of regional asset management at the Bandung Regency Education Office. This study uses a qualitative approach. Data collection was conducted through interviews, observations, and literature, as well as document analysis. The population and sample in this study were employees at the Bandung Regency Education Office who handle assets that are determined on a perpusive basis. The results show that SIMDA-BMD has succeeded in improving the accuracy of BMD inventory data and simplifying the digital asset management process. SIMDA-BMD also accelerates the reporting process and minimizes manual errors in data recording. For better BMD management, it is necessary to improve training for human resources, reduce reliance on manual recording, improve infrastructure, and evaluate to align the development and effectiveness of management.